Architecture as the art of creating human-friendly places - Chęć-Małyszek, Agnieszka (Budownictwo i Architektura / Civil and Architectural Engineering, 2021)
The public space of a city plays a special role in the life of every human being, as it meets basic and at the same time most important needs related to safety and comfort of life. It is a combination of an idea and a technique, which for centuries has reflected the changes taking place in people’s social and cultural life. While the city is a multi-layered structure with a clearly separated private and public zone, creating mutual relations between the buildings. Camillo Sitte saw the city urban spaces as a work of art, które should be designed in such a way that the inhabitants feel safe and happy, as it is not just a show-off of technical skill, but an artistic undertaking. [1] The art of designing architecture does not exist for itself, but is created for the target audience. It provides a harmony that satisfies human needs and guarantees survival. It is an important factor influencing the development of an individual through the organization of a social living space. Urban spaces are primarily people and their needs that change over time. The first part of the article is devoted to the role of public spaces and the idea of the city as a work of art. The second part, in turn, is an attempt to define architecture as a kind of fine arts, taking into account the role it plays in the social life of Lublin’s residents. The article is an attempts to emphasize the importance of architecture in designing a human-friendly environment as an art design that meets social expectations with the use of selected examples urban space of the city of Lublin.